Temperature, salinity and density of the surface waters of the Atlantic ocean. - Bohnecke, Gunther (New Delhi Oxonian Press, 1991)
Scientific results of the German Atlantic Expedition of the Research Vessel Meteor, 1925-1927; vol. 5 with atlas
Keywords: Reefs--Rota--Atlases.; Philippines--Maps.; Density--Atlantic ocean; Salinity--Atlantic ocean; Ocean temperature--Atlantic ocean